The role of early years care providers in supporting continued breastfeeding and breast milk feeding. Issue 2 (14th March 2020) - Dombrowski, Lindsay; Henderson, Susan; Leslie, Joyce; Mohammed, Khadija; Johnson, Dorothy; Allan, Nancy
Abstract: This paper discusses challenges faced by mothers who seek to continue breastfeeding and/or breast milk feeding (B/BMF) whilst using daytime childcare, and early years' practitioners' attitudes towards their role in the support of these feeding practices. The data-set being reported comes from a small-scale feasibility study that was conducted in the summer of 2015 at a childcare provider site in a highly deprived urban area of Scotland. Focus groups with B/BMF mothers, as well as with early years' practitioners were conducted. We report data pertaining to where responsibility lies for facilitating continued B/BMF, and on the perception of practitioners' attitudes, knowledge about, skills and providers' facilities for B/BMF. We recommend that care providers actively engage prospective parents in a discussion about how they can support continued B/BMF. These original data are contextualised and critically discussed within the wider literature with special attention being paid to the concept of unintended consequences.